2018
DOI: 10.1167/iovs.17-23312
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Molecular Screening in Chinese Usher Syndrome Patients

Abstract: PURPOSE. Usher syndrome (USH) refers to a group of autosomal recessive disorders causing deafness and blindness. The objectives of this study were to determine the mutation spectrum in a cohort of Chinese patients with USH and to describe the clinical features of the patients with mutations. METHODS.A total of 119 probands who were clinically diagnosed with USH were recruited for genetic analysis. All probands underwent ophthalmic examinations. A combination of molecular screening methods, including targeted n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
48
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(53 citation statements)
references
References 38 publications
2
48
0
Order By: Relevance
“…In our study, the patients with this mutation showed similar characteristics. In RP F3, the splice-site mutation c.8559-2A>G has been described in Japanese [19,20] and Chinese [10,14] USH II patients; however, this mutation is a frequent founder variant in Japanese USH II patients [20] and the most common mutation in Chinese USH II patients [10]. We have previously reported the presence of this mutation in combination with c.9570+1 G>A, another splice-site variant, in a USH II family [14].…”
Section: Discussionmentioning
confidence: 87%
See 3 more Smart Citations
“…In our study, the patients with this mutation showed similar characteristics. In RP F3, the splice-site mutation c.8559-2A>G has been described in Japanese [19,20] and Chinese [10,14] USH II patients; however, this mutation is a frequent founder variant in Japanese USH II patients [20] and the most common mutation in Chinese USH II patients [10]. We have previously reported the presence of this mutation in combination with c.9570+1 G>A, another splice-site variant, in a USH II family [14].…”
Section: Discussionmentioning
confidence: 87%
“…The two new splice-site mutations c.8682−1 G>T and c.22+3 A>G were each predicted to introduce an ectopic splice site. The previously reported splice-site mutation c.8559-2 A>G was detected in proband F3-II-2 [10,14,20]. An online splice-site prediction software program indicated that this variant would abolish the splice acceptor site in exon 43, resulting in the skipping of this exon.…”
Section: Identification Of Ush2a Gene Mutationsmentioning
confidence: 90%
See 2 more Smart Citations
“…It is found in 1 to 6% in the general population. However, in the Finnish and Ashkenazi Jews populations, it rises to about 40% [7][8][9][10]. So far, 13 genes have been identified to be involved in USH development (https://sph.uth.edu/ Retnet/sum-dis.htm).…”
Section: Introductionmentioning
confidence: 99%